Analisis Guncangan Eksternal Terhadap Indikator Moneter dan Makro Ekonomi Indonesia - Nora Ria Retnasih; Grisvia Agustin; Dwi Wulandari (Universitas Negeri Malang, 2016)
In accordance with the theory of a small open economy, Indonesia including the category of countries whose economies are vulnerable to the effects from another country who has a close working relationship, such as the United States of America (USA). The purpose of this study was to measure the effect of federal funds rate on BI rate; and BI rate implications on exchange rate, economic growth, and consumer price index. This type of research is quantitative. Collecting data using techniques of documentation provided by the Federal Reserve Data (FRED), Bank Indonesia (BI), and Bureau Central of Statistic (BPS). The analysis tool using Stationarity test, stability models test, determination of lag, and Structural Vector Autoregressive Models (svar). Based on the results of SVAR estimation can be concluded that Federal Fund Rate have a positive and significant effect on BI rate. By implication, BI rate have a positive and significant effect on exchange rate. However, BI rate has also positive but no significant effect on GDP. Neither CPI, the effect is negative and significant.Keywords: Federal Fund Rate, Exchange Rate, Gross Domestic Product, Consumer Prices Index, BI RateJEL Classification: E52, E60